Detection of Genus and Three Important Species of Cronobacter Using Novel Genus- and Species-Specific Genes Identified by Large-Scale Comparative Genomic Analysis - Wang, Lu; Wu, Pan; Su, Yingying; Wei, Yi; Guo, Xi; Yang, Lan; Wang, Min; Liu, Bin (Frontiers in Microbiology, 2022)
The genus Cronobacter includes seven species; however, the strains of C. sakazakii, C. malonaticus, and C. turicensis were highly correlated with clinical infections. Rapid and reliable identification of these three species of Cronobacter is important in monitoring and controlling diseases caused by these bacteria. Here, we identified four pairs of novel marker genes for the Cronobacter genus, C. sakazakii, C. malonaticus, and C. turicensis based on large-scale comparative genomic analysis from 799 Cronobacter and 136,146 non-Cronobacter genomes, including 10 Franconibacter and 8 Siccibacter, which are close relatives of Cronobacter. Duplex and multiplex PCR methods were established based on these newly identified marker genes. The reliability of duplex and multiplex PCR methods was validated with 74 Cronobacter and 90 non-Cronobacter strains. Strains of C. sakazakii, C. malonaticus, and C. turicensis could be detected accurately at both the genus and species level. Moreover, the newly developed methods enable us to detect 2.5 × 103 CFU/ml in pure culture. These data indicate that the accurate and sensitive established methods for Cronobacter can serve as valuable tools for the identification of these strains recovered from food, environmental, and clinical samples.